The use of aerosolized - Adrenergic agonist therapy after lung transplantation in pediatric age - Giorgia Grutter; Zaccaria Ricci (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
It is my opinion the use of aeresolized -adrenergic agonist such as salbutamol may be helpfull  not only  to reduced the early mortality but also  the chronic allograft dysfunction  after lung transplantation in children The reduction of pulmonary  edema could be prevent the induction of Obstructive Bronchiolites Syndrome (less pneumonia  and viral infections etc) such as the primary graft dysfunction.As we know by international literature Lung transplantation continues to suffer from less-than-ideal long-term outcomes, even in pediatric patients.